Conservation through co-occurrence: Woodland caribou as a focal species for boreal biodiversity. (April 2019) - Drever, C. Ronnie; Hutchison, Chantal; Drever, Mark C.; Fortin, Daniel; Johnson, Cheryl Ann; Wiersma, Yolanda F.
Abstract: Understanding how conservation of woodland caribou, an at-risk species for which large undisturbed areas are often proposed to maintain viable populations, can contribute to conservation of boreal biodiversity is an important consideration for an ecosystem warming at twice the global average and experiencing rapid resource development. We assess the focal or 'umbrella' value of the boreal population of woodland caribou for conservation of mammalian and avian richness (n = 432) in the boreal region of Canada by (i) evaluating co-occurrence of caribou distribution with that of boreal mammals (n = 102), birds (n = 330), at-risk mammals (n = 11) and at-risk birds (n = 47); and (ii) conducting systematic conservation planning using MARXAN software to identify minimum representative and complementary reserve networks, comprised of planning units deemed large enough (10, 000 km 2 ) for persistence of terrestrial wildlife, both at the extent of boreal caribou distribution and the entire boreal region. While boreal caribou overlap with the range of 90% of boreal birds and mammals, area-efficient networks representative of boreal diversity focus on species-rich areas south of caribou distribution and other areas that contain relatively small-ranged species. A similar pattern occurs when the MARXAN analysis focused only on caribou distribution, i.e. representative networks are preferentially located on southern herd ranges. However, this situation differs markedly to include large areas within the distribution of caribou if anthropogenic footprint on the landscape is considered as a constraint on reserve design. Efforts to sustain boreal caribou offer considerable opportunities to conserve diversity of co-occurring mammals and birds, including areas of the relatively more disturbed caribou southern ranges that have irreplaceable value in an efficient and representative pan-boreal network of reserves. The high focal value of boreal caribou for animal diversity should be considered when making decisions and policy choices about how to best allocate conservation efforts across its extensive distribution.